Chapter Als het met het onderwijs goed gaat, gaat het met ons ook goed Twee interviews over de Nederlandse educatieve uitgeefwereld - Graafland, Henriët (Amsterdam University Press, 2022)
This contribution consists of two interviews with experts from the Dutch educational publishing field. The first interviewee, Rivka Mooren, works as project editor Higher Education at Pearson Benelux. She explains how handbooks and digital learning platforms develop from the conceptual stage to publication. In light of international developments in higher education publishing, Mooren expects that the market will become fully digital, although in Europe more slowly than in the United States. Secondly, Regine Reincke considers the larger trends and developments in Dutch educational publishing. She works as Head of Product for ParnasSys, an administrative system for students that is widely used in Dutch primary schools. She arrived at this position after a career in educational publishing. This allows her to reflect on the role of technology in the classroom, and how it may enhance, but not replace, traditional classes and books.